2018
DOI: 10.3389/fncel.2018.00083
|View full text |Cite
|
Sign up to set email alerts
|

Substrates for Neuronal Cotransmission With Neuropeptides and Small Molecule Neurotransmitters in Drosophila

Abstract: It has been known for more than 40 years that individual neurons can produce more than one neurotransmitter and that neuropeptides often are colocalized with small molecule neurotransmitters (SMNs). Over the years much progress has been made in understanding the functional consequences of cotransmission in the nervous system of mammals. There are also some excellent invertebrate models that have revealed roles of coexpressed neuropeptides and SMNs in increasing complexity, flexibility, and dynamics in neuronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 220 publications
(420 reference statements)
5
101
0
Order By: Relevance
“…In both the larval and adult CNS, a large number of neurons innervating basically all neuropiles expressed svr PG33 ‐Gal4‐driven GFP (Figure a). This is in line with the idea that many Drosophila neurons express peptide co‐transmitters (Nässel, ). Due to the broad expression, it was impossible to identify specific arborisation patterns except for the tightly packed Kenyon cells with their parallel projections in the mushroom bodies (Figure a–c).…”
Section: Resultssupporting
confidence: 89%
“…In both the larval and adult CNS, a large number of neurons innervating basically all neuropiles expressed svr PG33 ‐Gal4‐driven GFP (Figure a). This is in line with the idea that many Drosophila neurons express peptide co‐transmitters (Nässel, ). Due to the broad expression, it was impossible to identify specific arborisation patterns except for the tightly packed Kenyon cells with their parallel projections in the mushroom bodies (Figure a–c).…”
Section: Resultssupporting
confidence: 89%
“…In both the larval and adult CNS, a large number of neurons innervating basically all neuropiles expressed svr PG33 -Gal4-driven GFP (Figure 4a). This is in line with the idea that many Drosophila neurons express peptide co-transmitters (Nässel, 2018).…”
Section: Svr Is Broadly Expressed Throughout the Larval And Adult Cnssupporting
confidence: 89%
“…We identified 28 neuropeptides that are expressed in at least one cell, at a 440 20 level of 10 or more transcripts per cell ( Figure 8A). Some neuropeptides are known to be 441 co-expressed with FANs, where they serve to increase signaling flexibility within neural 442 networks (Croset et al, 2018;Nässel, 2018;Nusbaum et al, 2017). We found that in the 443 VNC some neuropeptide genes are predominantly co-expressed with particular FANs, e.g.…”
Section: Peptidergic Neurons 435mentioning
confidence: 70%
“…High-level expression of neuropeptides 653 in this cluster is consistent with features of neurosecretory biology. Neuropeptides are 654 often produced by small numbers of cells, yet they can be broadly released and by volume 655 transmission and/or secretion into the hemolymph act at a distance to modulate disparate 656 neural circuits, physiological functions and behaviors (Nässel, 2018). The extraordinarily 657 high-level expression of pre-pro-neuropeptide genes in these cells suggests that 658 producing these molecules presents a considerable burden.…”
Section: Astrocytes and Ensheathing Glia 541mentioning
confidence: 99%